Occurrence of Rudderfish (Centrolophus niger Gmelin, 1789) in Saroz Bay (Northern Aegean Sea, Turkey) - Cengiz, Özgür; Paruğ, Şükrü Şenol; Kızılkaya, Bayram (Turkish Science and Technology Publishing (TURSTEP), 2019)
A single specimen of the rudderfish (Centrolophus niger Gmelin, 1789) was caught using the handline by fishermen on 14 April 2016 in İbrice Bight (Saroz Bay). This paper represents the first record of C. niger for Saroz Bay.
Keywords: saros bay; S; Agriculture (General); Agriculture; S1-972; centrolophus niger; turkey; rudderfish; northern aegean sea; 14. Life underwater